Estimating the thickness of the Martian subsurface layer based on the fault pattern - D Asahina; B Bradák; S Akdag; S Saydam (The Australasian Institute of Mining and Metallurgy, 2024)
Human exploration of Mars has been on the horizon of scientific goals for decades now, and as part of the objectives of human missions to various planets, one of the possible goals is opening new economic frontiers by the potential extraction and utilisation of resources, eg mining minerals and using surface regolith (Neukart, 2024). A comprehensive understanding of surface morphology, lithostratigraphy, basic structural geology, and civil engineering technology is essential to conduct mining operations for resource extraction on extraterrestrial planets. For instance, proper assessment of the risks associated with excavation and infrastructure construction under unique environments such as low gravity, surface irregularities, and the presence of regolith is fundamental. Such knowledge has been accumulated through satellite imagery and numerical topographic data using remote sensing technology, as well as seismic surveys by the on-site lander (Knapmeyer- Edrun et al, 2021; Banerdt et al, 2020; Giardini et al, 2020). Recent studies show that Marsquakes could be caused by the release of strain energy generated by the contraction of Mars. In particular, Marsquakes occur around the graben where many faults exist and form regularly spaced patterns. This implies that Marsquakes occur when the stress field of the Martian crust is an extension condition, and normal faults appear on the surface. In this study, we focus on so-called graben structures, one of Mars’s common tectonic structures (Plescia, 1991; Banerdt et al, 1992; Hoogenboom Hagen, 2014). The study aims to provide additional information about the tectonic environment during the formation of such features and, in addition, the internal mechanical-rheological structure of Mars, revealed by the geometrical pattern of faults modelled and simulated in a laboratory environment.